The Role of Rapid Automatized Naming in Children with Developmental Dysgraphia in German - Kaltenbrunner, Anna; Döhla, Diana; Heim, Stefan (Seminars in Speech and Language, 2025)
Various researchers have identified naming speed (rapid automatized naming [RAN]) as a predictor for reading skills and dyslexia. Although fewer studies investigate the connection between RAN and writing acquisition, their results suggest a connection between alphanumeric RAN tasks and spelling skills. Since the cognitive processes relevant to RAN have not yet been researched, it is unclear which components connect spelling performance and naming speed. Various authors propose a connection through orthographic and visual knowledge. This study investigated whether and how alphanumeric (letters and digits) and non-alphanumeric RAN (colors, objects) relate to spelling skills in German. Therefore, we investigated naming speed abilities in German 8- to 11-year-olds (n = 103) with pure developmental dysgraphia (i.e., isolated spelling deficit without reading deficit; n = 22), combined developmental dysgraphia and dyslexia (n = 26), and typical spelling and reading skills (n = 55). We found significant differences between children with pure developmental dysgraphia and children with typical reading and spelling skills for alphanumeric, but not non-alphanumeric RAN tasks. Our findings suggest that alphanumeric RAN, in contrast to non-alphanumeric RAN, is related to spelling. The study thus reveals the relevant difference between alphanumeric and non-alphanumeric RAN tasks and points toward distinct underlying cognitive mechanisms.
Keywords: literacy; development; spelling; reading; naming speed